The importance of Au⋯π(aryl) interactions in the formation of spherical aggregates in binuclear phosphane gold(i) complexes of a bipodal thiocarbamate dianion: a combined crystallographic and computational study, and anti-microbial activity - Yeo, C.I.; Khoo, C.H.; Chu, W.C.; Chen, B.J.; Chu, P.L.; Sim, J.H.; Cheah, Y.K.; Ahmad, J.; Halim, S.N.A.; Seng, H.L.; Ng, S.; Otero-de-la-Roza, A.; et al. (Royal Society of Chemistry, 2015)
Binuclear phosphanegold(i) complexes of a bipodal thiocarbamate dianion, (R3PAu)2L, R = Et (1), Ph (2) and Cy (3), where LH2 is {1,4-[MeOC(S)N(H)]2C6H4}, have been synthesised, and characterised spectroscopically (NMR and IR) and by X-ray crystallography. The gold atoms are linearly coordinated within a P-,S-donor set, and are oriented toward the central ring to form intramolecular Au ⋯π(aryl) interactions, rather than the intramolecular Au ⋯O interactions normally observed in mononuclear analogues. This phenomenon has been investigated by theory (LC-ωPBE-XDM) for 1 which revealed that the geometry optimised species with two Au ⋯π(aryl) interactions is more stable by at least 12 kcal mol-1 compared to conformations having one or more Au ⋯O interactions instead. The disk diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods were used to observe the inhibitory effect of complexes 1-3. The disk diffusion results demonstrated that 1 exhibited a broad spectrum of anti-bacterial activity toward 24 strains of Gram-positive and Gram-negative bacteria. By contrast, the anti-bacterial activity of 2 and 3 was limited to Gram-positive bacteria. Further evaluation showed that 1 exhibited marked bactericidal activity against B. cereus, B. subtilis, E. faecalis, L. monocytogenes, S. aureus, S. saprophyticus and methicillin resistant S. aureus cf. standard antibiotics tetracycline and chloramphenicol.